Digitisation and Low-Carbon Energy Transitions - Sareen, Siddharth; Müller, Katja (Springer Nature, 2023)
The world is digitising as the need for low-carbon transitions gains urgency. Decarbonising energy requires the digital process control of energy production, transmission and end use. Diversified electrification across sectors requires real-time digital coordination of distributed energy production, At the same time, digitisation is accompanied by significant increases in energy demand, partly compensated through energy efficiency gains. The emergent linkages between digitisation and decarbonisation - that constitute and enable the twin transition - are the subject of this book. The collection features authors from across the social sciences who situate digitisation and low-carbon energy transitions in the socio-technical and political economic contexts in which they unfold, to offer insights on the dynamics and contingencies of digitisation in and beyond the energy sector. This is an open access book.